Design and Feasibility of a Randomized Controlled Pilot Trial to Reduce Exposure and Cognitive Risk Associated With Advanced Glycation End Products in Older Adults With Type 2 Diabetes - Lotan, Roni; Ganmore, Ithamar; Livny, Abigail; Shelly, Shahar; Zacharia, Moran; Uribarri, Jaime; Beisswenger, Paul; Cai, Weijing; Schnaider Beeri, Michal; Troen, Aron M. (Frontiers in Nutrition, 2021)
Introduction: Advanced glycation end-products (AGEs) in diet and serum are positively correlated with chronic conditions such as type 2 diabetes and cognitive decline. Dietary reduction of AGEs was shown to reduce their level in serum and to have beneficial effect on metabolic biomarkers. However, in part due to limitations of feasibility, clinical trials have not tested its effect on cognition in elderly. The current pilot study examines the feasibility of AGEs reduction in elderly with diabetes in terms of recruitment and retention. Methods: The design is a randomized controlled pilot trial of dietary AGEs in elderly with type 2 diabetes (clinicaltrials.gov NCT02739971). Recruitment followed 2 stages: we first recruited participants with mild cognitive impairment and after expanding inclusion criteria we later recruited cognitively normal participants with subjective memory complaints. Participants were randomized to two arms. The control arm received standard of care guidelines for good glycemic control; the experimental arm, in addition to SOC guidelines, were instructed to lower their dietary AGEs intake, primarily by changing their cooking methods. Participants were closely followed for dietary adherence over6 months and evaluated before and after the intervention for adherence to the assigned diet, blood tests, cognitive performance, and brain MRI. Results: Seventy five participants (52 with mild cognitive impairment and 23 cognitively normal with subjective memory complaints) were recruited primarily through mass mailing and advertising in social media websites. Seventy participants finished the study and drop out was similar in both groups (7.5% in control vs. 5.7% in intervention p=0.757). The majority (57.5%) of participants in the AGEs-lowering arm showed very high adherence with the dietary guidelines. Discussion: Targeting feasible life style modifications in at high risk populations could prevent substantial cases of cognitive decline. Observational evidence supports that AGEs may contribute to cognitive decline ;however, the cognitive effect of reducing AGEs exposure has yet to be evaluated in a randomized controlled trial. The results of our pilot trial delineate a methodology including effective recruitment strategies, population of choice, and ways to assure high adherence during lifestyle modifications, and significantly advance progress toward a definitive and well-powered future randomized controlled trial.